KINEMATIC CHARACTERISTICS ANALYSIS OF RIGID⁃FLEXIBLE COUPLING SERIES⁃PARALLEL REHABILITATION MANIPULATOR - LI WenXia; ZHAO ZhiGang; ZHAO XiangTang; CHEN YiFan (Jixie qiangdu)
Aiming at the shortcomings of most of the current upper limb rehabilitation robots,this paper first designed a 4-DOF rigid⁃flexible coupled series⁃parallel rehabilitation robot arm with the advantages of rope drive and parallel structure.Secondly,under the condition of mapping relationship with joint space,the kinematic model of the rehabilitation manipulator was established by using the D⁃H coordinate method.Finally,in the Matlab environment,the relation between each joint angle,rope length and speed with time was simulated and analyzed.The analysis results show that the rationality of the structural design of the rigid⁃flexible coupling series⁃parallel rehabilitation manipulator is presented,and it also provides a theoretical basis for analyzing the trajectory planning of the rehabilitation manipulator.